Design of a tennis-specific agility test (TAT) for monitoring tennis players - Jansen, M. G.; Elferink-Gemser, M. T.; Hoekstra, A. E.; Faber, I. R.; Huijgen, B. C. (Journal of Human Kinetics, 2021)
Agility is an important ability for tennis players. To be successful in the rallies, players must perform rapid, multidirectional movements in response to the ball and/or the position of the opponent. For a test to be representative in monitoring agility performance, it should capture a combination of the physical and cognitive agility performance. Considering that literature reports no reliable and valid sport-specific agility test for tennis, the aim of this article was to design and evaluate the measurement properties of a Tennis-specific Agility Test (TAT). To evaluate the TAT, test-retest reliability, concurrent validity, and feasibility were assessed. For reproducibility, a two-way mixed ANOVA was performed. Concurrent validity was assessed using Pearson correlations. A total of 69 tennis players participated in this study of whom 16 competed at the international (22 ± 3.7 years, playing level (Dynamic Rating System): .8 ± .3), 43 at the national (14 ± 1.4 years, playing level: 4.6 ± 1.4), and 10 at the regional level (15 ± 0.8 years, playing level: 4.9 ± 1.1). Test-retest reliability was found to be moderate with an Intra-Class Correlation coefficient (ICC) of .74 (p < .01) and a percentual minimal detectable change (%MDC) of 6.2%. Concurrent validity was found to be moderate by comparison with a recognised agility test, the Spider Drill, which measures only the physical component (.70; p < .01), and by comparison with tennis performance for both boys (r = .67; p < .01) and girls (r = .72; p < .01). The feasibility was high with short time for preparation (five to ten minutes) and time per participant (<5 minutes). In conclusion, the TAT shows promising results for assessing sport-specific agility performance in tennis making it likely to be used in the practical setting.